Potential of Atlantic Codfish (Gadus morhua) Skin Collagen for Skincare Biomaterials - Cristina V. Rodrigues; Rita O. Sousa; Ana C. Carvalho; Ana L. Alves; Catarina F. Marques; Mariana T. Cerqueira; Rui L. Reis; Tiago H. Silva (Molecules, 2023)
Collagen is the major structural protein in extracellular matrix present in connective tissues, including skin, being considered a promising material for skin regeneration. Marine organisms have been attracting interest amongst the industry as an alternative collagen source. In the present work, Atlantic codfish skin collagen was analyzed, to evaluate its potential for skincare. The collagen was extracted from two different skin batches (food industry by-product) using acetic acid (ASColl), confirming the method reproducibility since no significant yield differences were observed. The extracts characterization confirmed a profile compatible with type I collagen, without significant differences between batches or with bovine skin collagen (a reference material in biomedicine). Thermal analyses suggested ASColl’s native structure loss at 25 °C, and an inferior thermal stability to bovine skin collagen. No cytotoxicity was found for ASColl up to 10 mg/mL in keratinocytes (HaCaT cells). ASColl was used to develop membranes, which revealed smooth surfaces without significative morphological or biodegradability differences between batches. Their water absorption capacity and water contact angle indicated a hydrophilic feature. The metabolic activity and proliferation of HaCaT were improved by the membranes. Hence, ASColl membranes exhibited attractive characteristics to be applied in the biomedical and cosmeceutical field envisaging skincare.